Discursos Jornalísticos sobre a Independêcia de Moçambique – Uma análise da cobertura do semanário savana (1998-2003) - João Feijó (Cadernos de Estudos Africanos)
In the late 1990’s Mozambique celebrated its independence silver jubilee, in a context of recent economic openness and liberalization. The country began to take the first steps of a democratization process and the independent press arose the first debates where were facing opposite opinions on the country development. It is in this context that we wished to examine the speeches at the weekly Savana on the occasion of the Mozambican historical celebrations, in order to understand the country independence assessment. Beyond an analysis of the social representations of the past, throughout this article we will take into account the opinion makers motivations and expectations.